Assessment of the attractiveness of construction technologies in conditions of socio-environmental limitations - Shpakova, H. V. (Ways to Improve Construction Efficiency, 2018)
The article considers the variant indicators of the assessment of production (in particular, construction) technologies used for the production of products on the principles of sustainable development. The greening of the construction industry, aimed at minimizing the use of natural resources, must proceed by replacing the existing linear production model with a circular economic model as the most appropriate resource-saving requirement. Ways of introduction of the strategy of ecological construction for the construction industry of Ukraine are proposed while involving in the process of new construction and modernization by the development companies the mechanisms of recycling of building structures, products and materials.